Intracellular antioxidant activity of Muntingia calabura leaves methanolic extract - AULIA NUR RAHMAWATI; OKID PARAMA ASTIRIN; ARTINI PANGASTUTI (Nusantara Bioscience, 2018)
Rahmawati AN, Astirin OP, Pangastuti A. 2018. Intracellular antioxidant activity of Muntingia calabura leaves methanolicextract. Nusantara Bioscience 19: 210-214. Excessive reactive oxygen species (ROS) results in oxidative damage that destroys proteins,lipids, and DNA, resulting in various diseases and accelerating the aging process. Antioxidants are compounds that have the ability tosuppress oxidative stress. Muntingia calabura has a high phytochemical content, especially the phenolic group that can act asantioxidant. This study aimed to determine the intracellular antioxidant activity of M. calabura leaves methanolic extract (MLME)through intracellular ROS levels in 3T3 fibroblast cells under normal condition and oxidative stress due to UVB exposure. Tests wereperformed using the DPPH (Diphenyl-1-picrylhydrazyl) method and modified NBT (Nitroblue Tetrazolium). Testing of antioxidantactivity with DPPH method obtained result that MLME had high antioxidant activity with IC50 value of 3.030 ?g mL-1, whileintracellular antioxidant activity with modified NBT method showed that MLME statistically had significant effect on intracellular ROSlevel under normal condition (p < 0.05) based on dose-dependent manner, but not significant (p > 0.05) under oxidative stress condition.Significant effects were only shown at a concentration of 20 ?g mL-1 against the control of oxidative stress due to UVB exposure.